Noni Fermentation as an Effort to Prevent COVID 19 in Sidoarjo, Indonesia - Ainun Ridhotillah; Endang Wahju Andjariani; Ettyani Ettyani (Universitas Muhammadiyah Sidoarjo, 2021)
Covid 19 epidemic has made people more aware of the importance of health and personal hygiene. They strive to increase body immunity against various viruses, bacteria, and germs. One of the plants capable of improving body immunity is noni plant. It is much likely to prevent corona virus. Noni fruit contains substance capable of preventing cancer and antimicrobials. skopoletin dan anthraquinon of noni fruit has anti-septic substance that can kill bacteria and fungi in the body. Alkaloid of morinda citrifolia is also effective to increase immunity and to lower cholesterol. Due to its anti-virus property, noni can also cure fever, pain, and cough. For noni fermented beverage, the analysis of SWOT (Strength, Weakness, Opportunities, Threats) has been made for its potential market. The fermented noni drink is expected to be an alternative herbal drink which is healthy and economic-valued. This product is also expected to inspire an innovative enterpreneurship. By making use of often-discarded-noni fruit into fermented noni beverage, people can employ others as noni fruit collectors, thus employment created. The manufacture of the product includes pre-production stage, fermentation production, packaging, promoting, launching, and to the post-production stage. The fermented noni has its particular blend of fresh and sweet flavors. Consumers may get attracted to buy this rich-nutrient herbal drink. The manufacture of fermented noni drink can empower the people of desa pagerngumbuk. They can start by planting the noni plant. Hence, it is expected to make a new enterpreneuship activity among the society of desa Pagerngumbuk. This can be initiated particularly by the women of PKK.